Evaluasi Tata Kelola Sistem Keamanan Teknologi Informasi Menggunakan Indeks KAMI dan ISO 27001 (Studi Kasus KOMINFO Provinsi Jawa Timur) - Edo Rizky Pratama; Suprapto Suprapto; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Dinas Komunikasi dan Informatika (KOMINFO) Provinsi Jawa Timur is a government agency in the field of communications and informatics as well as providing public services. KOMINFO has a data center that manages information from all IT services and devices in KOMINFO's office, the data center manages a lot of important and valuable information which must be secured with clear standards. Based on interviews that have been done, KOMINFO shall do information security in accordance with Peraturan Menteri Komunikasi dan Informatika Republik Indonesia Nomor 4 Tahun 2016, other than that KOMINFO will also conduct an ISO 27001 certification on information security. Therefore, the purpose of this research is to evaluate the security of existing information using the Indeks KAMI and then see the results of the completeness and maturity of information security in the 5 areas of the Indeks KAMI and the feasibility of KOMINFO to perform ISO 27001 certification. From the evaluation results known about the maturity level of each information area at the I+ level and overall KOMINFO is not feasible to perform ISO 27001 certification. The result is the basis for making recommendations. The recommendations are made by comparing the shortcomings of the existing areas of the Indeks KAMI with the controls that exist in ISO 27001. One of the recommendations provided is that KOMINFO should implement detection, prevention and restoration controls to protect facilities against malware.